PSA density as a parameter in prostate biopsy decision of patients with prostate sized 80 mL or larger - Ediz, Caner; Cimen, Serhan; Akan, Serkan; Temel, Muhammed Cihan; Yilmaz, Omer; Koksal, Ozlem (International Journal of Research in Medical Sciences, 2019)
Background: Patients with high prostate volume (>80 ml) and high PSA levels make it difficult to decide on prostate biopsy. In this study, author aimed to detect of predictive factors to distinguish malignant or benign prostatic lesions in patients with prostate size over 80 ml. Methods: A total of 299 patients underwent TRUSBP at the clinics between 2012-2017. Cases with prostate volume over 80 ml were divided into groups according to the pathology by benign (group 1) or malign (group 2). Author evaluated the predictive factors in two groups. Patient’s age, grading and findings of digital rectal examination, prostate volume, number of received cores, total (tPSA) and free PSA (fPSA) before biopsy, rate of percentage of free to total prostate specific antigen (f/tPSA) and PSA density was compared in both groups. Results: Benign prostate hyperplasia was detected in 217 patients (72.58%) and prostate adenocarcinoma was detected in 82 patients (27.42%). The patient’s age, tPSA, fPSA and PSA density were 63.81 years, 9.71 ng/ml, 1.78 ng/ml and 0.10 g/ml2 in group 1 and 69.10 years, 38.32 ng/ml, 5.86 ng/ml and 0.42 ng/ml2 respectively. Patient’s age, tPSA, fPSA and PSA density was statistically significant between in two groups (p<0,05). Number of received cores and rate of f/tPSA were 14.02-13.84% and 19.06-17.62% in group 1 and 2, respectively and was not statistically significant. In group 2, prostate adenocarcinoma was most common detected with Gleason score 4+3 in 21 of 82 patients (25.6%). Conclusions: High prostate volume (>80 ml) has a significant influence in PSA values and results of the biopsy, PSA density is extremely important in performing prostate biopsy decisions.